PENDAMPINGAN PENERAPAN STRATEGI PENGEMBANGAN DALAM PENGELOLAAN DAN PEMANFAATAN EKOSISTEM MANGROVE SEBAGAI DAERAH EKOWISATA BERBASIS MASYARAKAT DI DESA LONTAR KABUPATEN SERANG - Khaeruman Khaeruman; Ade Fauji; Syamsul Hidayat; Ombi Romli; Mochamad Fahru Komarudin; Yuliah Yuliah; Suflani Suflani (Yayasan Education and Social Center, 2022)
The aim of this program is to improve the skills and sensitivity of the team of practitioners in the design of concepts and strategies in the management and use of mangrove forest ecosystems as a field of community-based ecotourism. Output targets include; Increased knowledge about the potential of mangrove ecosystems that have the value of environmental services that can be managed and used as an ecotourism field in accordance with community participation and empowerment. With the implementation of this program, a form of strategy is obtained in the management and use of community-based mangrove ecosystems and assistance for local government programs in the context of mangrove ecosystem preservation that have been regulated in regional regulations on the management and preservation of mangrove ecosystems. The method of implementing the program concerns the potential of forest areas that can be used as ecotourism areas in this case, the village government of Serang Regency, Tirayasa District, direct observation and documenting the location of mangrove ecosystem areas, plan interviews concerning the management and use of mangrove ecosystems as a field of community-based ecotourism, and socialization of mangrove ecosystem management and use as an ecotourism field based on community strengthening and Institutional. The results of the program obtained consist of a plan to manage and use the mangrove ecosystem as a community-based ecotourism field. This design will be a model that can be used by partners in this case the Lontar village government in Tirayasa District, Serang Regency in the development of mangrove ecosystems as an ecotourism area. The design to explore the management of plans and the use of mangrove ecosystems as ecotourism areas has been socialized by community leaders, youth leaders and village governments